2000
DOI: 10.1046/j.1365-2672.2000.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

One explanation for the variability of the bacterial suspension test

Abstract: M BE RT . 2000. Disinfection kinetic studies of sodium dodecyl sulphate, benzalkonium chloride and sodium hypochlorite against Staphylococcus aureus revealed that when a higher inoculum level of Staph. aureus than normal was used (approximately 1 log higher), the efficacy of disinfection was severely attenuated. Kinetic analysis using the Hom model for experiments carried out on tests using 3 × 10 8 organisms ml −1 were unable to account for the large increase in disinfection power observed when smaller inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
3
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 12 publications
1
48
3
1
Order By: Relevance
“…As a result, despite the similar inactivation rates, the populations of two competing strains in SGF could be different at each time point due to differences in their initial cell density (e.g., see the case of C5 plus 6179). Previous studies have suggested that the inoculum size can affect bacterial inactivation kinetics with lower inocula, resulting in faster inactivation (28,36). On the other hand, we showed that after 6 or 8 days of cocultivation in TSB-Y, the lower population levels of ScottA compared to C5 or PL25 populations did not lead to faster elimination of ScottA in SGF.…”
Section: Discussioncontrasting
confidence: 49%
“…As a result, despite the similar inactivation rates, the populations of two competing strains in SGF could be different at each time point due to differences in their initial cell density (e.g., see the case of C5 plus 6179). Previous studies have suggested that the inoculum size can affect bacterial inactivation kinetics with lower inocula, resulting in faster inactivation (28,36). On the other hand, we showed that after 6 or 8 days of cocultivation in TSB-Y, the lower population levels of ScottA compared to C5 or PL25 populations did not lead to faster elimination of ScottA in SGF.…”
Section: Discussioncontrasting
confidence: 49%
“…Like other antibacterial agents, susceptibility to QACs may be based on the ability of QACs to kill microorganisms and/or to inhibit growth, depending on the purpose. The testing conditions can highly influence the results; thus, it is difficult to compare results between investigations and to extrapolate from laboratory to practical conditions [21][22][23][24][25]. The most influential test conditions include temperature, time of exposure, amount of organic material, growth conditions and growth phase of the microorganism to be tested.…”
Section: Quaternary Ammonium Compound Susceptibility Testingmentioning
confidence: 99%
“…Undoubtedly, test heterogeneity jeopardises clear interpretation of the available data [21][22][23][24][25]. Laboratory assays currently available include MIC tests for QACs, biocidal tests (i.e.…”
Section: Recommendationsmentioning
confidence: 99%
“…Considerable variability was observed in the survival of L. monocytogenes, Staph. aureus, and S. enterica between biological replicates; these results are likely the result of either differences in medium composition [i.e., redox, level of oxygen, and (or) level of nutrients] or physiological differences in the inocula (i.e., initial cell number or growth phase; Johnston et al, 2000). This variability also has affected studies done in natural cheeses (Shrestha et al, 2011a,b;Hystead et al, 2013).…”
Section: Phase 1: Survival and Growth Of 4 Select Bacterial Pathogensmentioning
confidence: 99%